Privatization in an international mixed duopoly with environmental taxes - Ferreira, Flávio (2015)
We study the effects of environmental and trade policies in an international duopoly serving two countries, with pollution abatement. This analysis is done in both mixed and privatized markets. The model has two stages: First, governments choose environmental taxes and import tariffs, simultaneously; then, the firms compete in the market by choosing output levels for the domestic market and to export and also abatement levels.